2015
DOI: 10.1002/2015ja021097
|View full text |Cite
|
Sign up to set email alerts
|

Cassini VIMS observations of H3+ emission on the nightside of Jupiter

Abstract: We present the first detailed analysis of H3+ nightside emission from Jupiter, using Visual and Infrared Mapping Spectrometer (VIMS) data from the Cassini flyby in 2000–2001, producing the first Jovian maps of nightside H3+ emission, temperature, and column density. Using these, we identify and characterize regions of H3+ nightside emission, compared against past observations of H3+ emission on the dayside. We focus our investigation on the region previously described as “mid‐to‐low latitude emission,” the sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Where e * is a fast electron and EUV is an extreme ultraviolet photon from the Sun. As soon as H + 2 is created by reactions (1) -(3), reaction 4takes place almost instanteously (Miller et al, 2010;Stallard et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Where e * is a fast electron and EUV is an extreme ultraviolet photon from the Sun. As soon as H + 2 is created by reactions (1) -(3), reaction 4takes place almost instanteously (Miller et al, 2010;Stallard et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…[]; in this work values < 350 K are reported, while temperatures as high as 500–850 K were observed on the bright 3 µm spots imaged using the Gemini Near‐InfraRed Spectrograph data. Also the H 3 + temperatures retrieved in our study are systematically lower than those reported in the literature for the VIMS spectra [ Stallard et al ., ] and ground‐based data [ Lam et al ., ; Stallard et al ., ; Raynaud et al ., ; Lystrup et al ., ] which are around 800–1000 K. We have repeated the analysis of the spectrum of the orange area including only H 3 + in the simulation. In this case the H 3 + retrieved temperature is 1109.10 ± 32.2 K, closer to the one obtained by previous works.…”
Section: Discussionmentioning
confidence: 98%
“…Lower concentrations of H 3 + make up the disk population in Jupiter's ionosphere. This population is generated from the fast chain reaction beginning with ionization by solar EUV [ Lam et al , 1997; Miller et al , 1997], as shown in equation , and does not exist in the nightside ionosphere of Jupiter [ Stallard et al , 2015]. H 2 + e H 2 + + e + e H 2 + italichν H 2 + + e H 2 + + H 2 H 3 + + normalH …”
Section: Introductionmentioning
confidence: 99%